Gradient Estimates for Weak Solutions of 𝒜-Harmonic Equations. (30th May 2010) - Yao, Fengping
Abstract : We obtain gradient estimates in Orlicz spaces for weak solutions of𝒜 -Harmonic Equations under the assumptions that𝒜 satisfies some proper conditions and the given function satisfies some moderate growth condition. As a corollary we obtainL p -type regularity for such equations.